DEPDC5 mutations in familial and sporadic focal epilepsy - Tsai, Meng Han; Chan, Chung Kin; Chang, Ying Chao; Yu, Y.T.; Chuang, S.T.; Fan, W.L.; Ling, S.C.; Fu, Ting Ying; Chang, Wen Neng; Liou, Chia Wei; Chuang, Yao Chung; Ng, Ching Ching; et al. (Wiley, 2017)
Background and Aims: Mutations in the disheveled, Egl-10 and pleckstrin domain-containing protein 5 (DEPDC5) gene have emerged as an important cause of various familial focal epilepsy syndromes. However, the significance of DEPDC5 mutations in patients with sporadic focal epilepsy has yet to be characterized. Materials and Methods: We studied a kindred of familial focal epilepsy with variable foci using whole-exome sequencing. We subsequently studied a cohort of 293 patients with focal epilepsy and sequenced all exons of DEPDC5 using targeted resequencing. Results: We reported a Taiwanese family with a novel splice site mutation which affected mRNA splicing and activated the downstream mammalian target of rapamycin (mTOR) pathway. Among patients with focal epilepsies, the majority (220/293) of these patients had sporadic focal epilepsy without malformation of cortical development. Two (0.9%) of these patients had probably pathogenic mutations in the DEPDC5 gene. Discussion and Conclusions: Our finding suggests that DEPDC5 is not only the most common gene for familial focal epilepsy but also could be a significant gene for sporadic focal epilepsy. Since focal epilepsies account for more than 60% of all epilepsies, the effect of mTORC1 inhibitor on patients with focal epilepsy due to DEPDC5 mutations will be an important future direction of research.